ANALISIS KINERJA KEUANGAN PERUSAHAAN PT NIPPON INDOSARI CORPINDO TBK ( DITINJAU DARI LIKUIDITAS, SOLVABILITAS & PROFITABILITAS ) - Muhammad Setiadi Hartoko (JURNAL LENTERA AKUNTANSI, 2013)
Aims of this study are to analyse the financial performance of PT Nippon Indosari Corpindo Tbk In Bekasi, West Java in paying short-term liabilities by using the ratio of liquidity, to assess financial performance of PT Nippon Indosari Corpindo Tbk In Bekasi, West Java in accomplishing debts if the company got liquidated by using the ratio of solvency, and to analyse its performance in generating profits by using the ratio of profitability. Tools of analysis used to assess company's financial performance are the ratio of liquidity, the ratio of solvency and the ratio of profitability. Analysing PT Nippon Indosari Corpindo Tbk In Bekasi, West Java by using the ratio of liquidity has shown that current ratio and Cash Ratio indicates that the company has owned a poor-managed performance since it still has disability to pay its current liabilities by using current assets possessed. According to the ratio of solvency, Increase of ratio of Total Debt to Total Assets and Total Debt to Equity shows that the company has managed poor for it can cover its debts by managing its assets. By looking at analysis of the ratio of profitability, Return on Assets and Return on Equity is decline in each year points out a poor performance of the company. Even though its profit has increased year by year but it is not comparable to the larger assets for the company does not maximize in making profit. Keywords: Ratio of liquidity, ratio of solvency, ratio of profitability.